Acute effect of partial body weight suspension on the level of cocontraction and gait biomechanics in women with knee osteoarthritis - Hebling Spinoso, Deborah (2020)
Introduction: Knee osteoarthritis (OAK) is one of the most prevalent rheumatic diseases in the population, characterized by functional limitation and gait difficulties with profound clinical relevance, as walking is the most frequently performed daily activity. These functional limitations may be more pronounced when the disease is associated with obesity. Objective: To investigate the effect of different body weight suspension percentages on gait biomechanical variables and co-contraction percentages in women with OAK. Method: Fourteen women aged 50-75 years, with a body mass index between 26 and 35 and radiological diagnosis of OAK participated in the study. On the first day, anamnesis and familiarization with gait on the treadmill was performed. On the second day, treadmill gait assessment was performed using partial body weight support (SPPC) in three conditions-15%, 30%, and 45% suspension. During the evaluation, electromyographic and kinematic data were collected. The variables analyzed were percentage of hip (gluteus maximus/rectus femoris), knee (femoral biceps/vastus lateralis), and ankle (anterior tibial/lateral gastrocnemius), and length and step widths. A one-way analysis of variance was conducted, with a significance level of p < 0.05. Results: There was no significant difference in the length and step width and the level of co-contraction between the running conditions analyzed. Conclusion: Body weight suspension using SPPC during treadmill running did not alter the biomechanical variables of the gait of women with OAK.